TANJUNGPURA SCIENCE AND TECHNOLOGY LABORATORY - Andyani Eka Lestari; Lestari Lestari; Irwin Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Along with the rapid development of Science and Technology (IPTEK) globally, which seems to spread to various segments in the world, it creates competition for every country to take part in the progress of science and technology. To achieve this goal, a mature strategy is needed for equitable distribution of science and technology, a good synergy between institutions and human resources is needed. West Kalimantan has the potential in terms of territory and existing human resources to have the development center, because Universitas Tanjungpura is the largest university in West Kalimantan which has the potential to become a center for science and technology activities, of course with flexible laboratory facilities as a forum for development. The purpose of this design is to produce a design for the Tanjungpura Science and technology laboratory building. Design starts from determining the problem in the design, collecting primary and secondary data related to the design process. Primary data in the form of a field survey on Jl. Prof. Dr. Hadari Nawawi and secondary data from books, journals, and data from related institutions. The data is then processed and analyzed to produce floor plans, views, section and the perspective of exterior and interior. Adaptable architecture design considering physical aspects, spatial aspects, building character and contextual aspects in the design process. This concept resulted in a building design consisting of several separate masses then connected by bridges to achieve spatial attachment, flexible spaces that are comfortable and safe for users and their environment. Standarized and adaptability are the core of the Tanjungpura Science and technology laboratory design